Rethinking Posisi Mahram Pria Dalam Fiqih Safar Perempuan (Membendung Feminisasi Pengangguran Dengan Analisis Hukum Kritis) - Tobroni, Faiq (Musawa Jurnal Studi Gender dan Islam, 2010)
According to a hadits three main factors making a man to become a "mahram" for women are: direct kinship, marriage and breastfeding. The concept of "mahram" doesn't only effect the provisions of marriage, according to some opinions, but also effects woman's chance of working in public. It is here where the dispute about woman's permissibility to go far away (safar) without her "mahram" arising. Those who only conclude the hadits literally forbid woman to travel without "mahram". Those conclude contextually as well as essentially tend to permit woman to go far away whitout "mahram". According to latter, the role of "mahram" in protecting woman can be substituted to the state. This paper doesn't only explore the substantial advice of concept of "mahram" but also analyzes it in the perspective of critical legal studies. I think this analysis is very important to produce an "ijtihad" siding with woman, appreciating the development of society and regulating the progressive law (regulatingnot only a obligation "wujUb" and a prohibition "tahnm" but also a recommendatian "nadb", mere permissibility "ibahah" and abomination "karahah").